Effect of non-genetic factors on various Reproduction traits in Murrah Buffaloes - jamal, ishfaq; Mehla, Dr R K; yousuf, saleem; naik, Muzaffar ahmad; japeth, K. Puhle (Indian Journal of Dairy Science, 2018)
Data of 742 Murrah Buffalo cows spread over a period of 16 years (1999- 2013) were collected and analysed to examine the effect of non-genetic factors on different reproduction traits. The Overall least square means of age at first calving (AFC), service period (SP), dry period (DP) and  calving interval (CI), were 1398.67±7.2 days, 147.85±2.12 days, 121.68±1.39 days and  455.041±3.14 days, respectively. Effect of period of birth was significant (P˂0.01) on age at first calving (AFC), while period of calving has significant effect (P